Analisis Sejarah Sosial Masyarakat Batubara Serta Dinamika Etnis dalam 'Mission to The East Coast of Sumatra' oleh John Anderson (Abad Ke-19) - Maulana, Imran; Siregar, Yusra Dewi; Nasution, Kasron Muhsin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Batubara community on the east coast of Sumatra possesses a unique cultural heritage and social structure, yet it remains insufficiently examined from a social-historical perspective. John Anderson’s travel account in Mission to the East Coast of Sumatra (1823) provides important insights into social life, traditional leadership, and interethnic dynamics in Batubara during the early 19th century. This study aims to uncover the social history of the Batubara community and to analyze patterns of ethnic dynamics that occurred within colonial and regional contexts as reflected in Anderson’s work. This research employs a qualitative method with a content-analysis approach to colonial texts as primary sources, supported by secondary data such as interviews with local figures and historical documentation. The findings show that the social structure of the Batubara community was built upon the Kedatukan system led by the Datuk Empat Suku, who held not only customary authority but also political and religious functions. Furthermore, ethnic dynamics in Batubara unfolded through interactions among Malay, Batak, and other groups, which fostered cultural acculturation, economic collaboration, and occasional social tensions that were addressed through local diplomatic strategies. Anderson’s representation of Batubara reveals a colonial perspective that tends to be biased, yet still offers significant ethnographic value for reassessing local history. Thus, this study affirms that a social-historical approach can effectively reconstruct collective identity and intergroup relations within the context of colonialism in East Sumatra.